The landscape of utopia writings on everyday life, taste, democracy, and design - Waterman, Tim (Routledge, Taylor & Francis Group, 2022)
"A collection of short interludes, think pieces, and critical essays on landscape, utopia, philosophy, culture, and food, all written in a highly original and engaging style by academic and theorist Tim Waterman. Exploring power and democracy, and their shaping of public space and public life; taste, etiquette, belief and ritual, and foodways in community and civic life, the book provides a much-needed critical approach to landscape imaginaries. It discusses landscape in its broadest sense, as a descriptor of the relationship between people and place that occurs everywhere on land, from cities to countryside, suburb to wilderness. With over fifty black and white illustrations interspersing the twenty-six chapters, this is a book for professionals, academics and students to dive into and spark discussion on new modes of thinking in the wake of unfolding global crises, such as Covid-19, climate change, fascism 2.0 and beyond"--
Keywords: Kultur; Landschaft; Social ecology; Manners and customs; Political sociology; Landscape architecture / Philosophy; Eating (Philosophy); Utopias; Social Environment; Cultural Characteristics; Écologie sociale; Murs et coutumes; Sociologie politique; Architecture du paysage / Philosophie; Nourriture; Utopies; human ecology